ANALISIS KINERJA BOILER DI PT. PLN (PERSERO) WILAYAH KALIMANTAN SELATAN KALIMANTAN TENGAH SEKTOR PLTU ASAM - ASAM - Jenta Yudi Perageminisko; Aqli Mursadin (JTAM ROTARY, 2019)
Boiler is a tool that serves to convert water into pressurized steam. In the heat causes heat boiler heat transfer through the water into pressurized steam that is heated from the fuel in the furnace.And often a problem of burning in the boiler is less than the maximum. Because the incoming energy is energy derived from the fuel, there is some energy lost during the combustion process it happens because the fuel has a low heat so that the combustion is not maximal cause the boiler performance is reduced. To avoid this, it is necessary to  maintenance for the boiler component in order to improve performance. Direct method is "input - output method" because this method uses only the heat in the fuel and steam coming from the boiler output. Boiler efficiency of research results from the date of March 27, 2017 until the date of 10 April 2017 with a total average - average efficiency were analyzed, namely 74.4%. On April 3, 2017 the calculated efficiency of 76.57% indicates that the boiler performance is still feasible to operate but on April 4, 2017 the boiler efficiency becomes 71.59%. Boiler efficiency at commissioning, with boiler efficiency of 85.13% and in 2017 done the boiler efficiency calculation theoretically on 27 March until 10 April 2017 with total average 74.4% where the efficiency decrease equal to 10.73%. Factors affecting the efficiency ratio are in the coal content used. Keywords:Boiler, Performance, Direct Method